Resin composition

JP2025031440AInactive Publication Date: 2025-03-07NANYA PLASTICS CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023190531
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-23
Filing Date
2023-11-08
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Benefits of technology

【0013】 上記に基づき、本発明の樹脂組成物は、反応の間に極性基を形成しない特性を有し、電界において容易に分極することはなく、これにより誘電正接を大幅に減少させる。加えて、本発明の樹脂組成物は、銅箔基板に応用されるとき、高ガラス転移温度(260℃以上)、低誘電率(3.5以下)、及び低誘電正接(0.003以下)を達成することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025031440000001
    Figure 2025031440000001
  • Figure 2025031440000002
    Figure 2025031440000002
  • Figure 2025031440000003
    Figure 2025031440000003
Patent Text Reader

Abstract

To provide materials that have excellent electrical properties and meet the characteristic requirements of high-frequency printed circuit boards.SOLUTION: The disclosure provides a resin composition which includes: 30 wt.% to 50 wt.% of a bismaleimide resin; 1 wt.% to 10 wt.% of an epoxy resin; 1 wt.% to 10 wt.% of a benzoxazine resin; 1 wt.% to 5 wt.% of a hardener; 10 wt.% to 40 wt.% of a filler; and 0.1 wt.% to 3 wt.% of a coupling agent, based on the total weight of the resin composition.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition, and in particular to a resin composition. [Background technology]

[0002] In recent years, with the development of 5G communication and millimeter wave communication, higher frequencies (6 to 77 GHz) are being applied to mobile phones, base stations, servers, etc., and it is necessary to use board materials for higher frequencies to be suitable for 5G high frequencies. Conventional epoxy resins have a dielectric constant of 3.5 to 5.0 and a dielectric loss tangent higher than 0.01, which is not sufficient for the rapidly developing high-frequency communication applications. In addition, the direct application of amine curing agents and phenolic resin curing agents to copper foil boards cannot overcome the drawback of high transmission loss. For this reason, it is necessary to develop materials that have excellent electrical properties such as high glass transition temperature, low dielectric constant, and low dielectric loss tangent, and that meet the property requirements of high-frequency printed circuit boards. Summary of the Invention [Problem to be solved by the invention]

[0003] The present invention provides a resin composition, comprising, based on the total weight of the resin composition, 30 wt % to 50 wt % of a bismaleimide resin, 1 wt % to 10 wt % of an epoxy resin, 1 wt % to 10 wt % of a benzoxazine resin, 1 wt % to 5 wt % of a curing agent, 10 wt % to 40 wt % of a filler, and 0.1 wt % to 3 wt % of a coupling agent. [Means for solving the problem]

[0004] In one embodiment of the invention, the bismaleimide resin comprises DCPD-BMI, KI-50P, KI-70, MIR-3000, MIR-5000, or a combination thereof.

[0005] In one embodiment of the present invention, the weight percentage of the epoxy resin is 1% to 3% by weight.

[0006] In one embodiment of the present invention, the resin composition further comprises 0.1% by weight to 3% by weight of a catalyst.

[0007] In one embodiment of the present invention, the resin composition further contains 5% by weight to 15% by weight of a flame retardant.

[0008] The present invention provides an electronic component including a substrate formed from the resin composition.

[0009] In one embodiment of the invention, the substrate has a dielectric constant of less than or equal to 3.5 at a frequency of about 10 GHz.

[0010] In one embodiment of the invention, the substrate has a dielectric loss tangent of less than or equal to 0.003 at a frequency of about 10 GHz.

[0011] In one embodiment of the invention, the glass transition temperature of the substrate is 260° C. or higher.

[0012] In one embodiment of the invention, the substrate is a copper foil substrate. Effect of the Invention

[0013] Based on the above, the resin composition of the present invention has the property of not forming polar groups during the reaction, and is not easily polarized in an electric field, thereby greatly reducing the dielectric loss tangent. In addition, when the resin composition of the present invention is applied to a copper foil substrate, it can achieve a high glass transition temperature (above 260°C), a low dielectric constant (below 3.5), and a low dielectric loss tangent (below 0.003). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The following describes in detail the embodiments of the present invention. The implementation details provided in the embodiments are for illustrative purposes, and are not intended to limit the protection scope of the present invention. Those skilled in the art can modify or change these implementation details according to the actual implementation requirements.

[0015] Ranges may be expressed herein as from "about" one particular value to "about" another particular value, which may be expressed directly as the one particular value and / or the other particular value. When a range is expressed, in another embodiment, it includes the one particular value and / or to the other particular value. Similarly, when values ​​are expressed as approximations, by use of the antecedent "about," it is to be understood that the particular value forms another embodiment. It is to be further understood that the endpoints of each range may or may not be expressly related to the other endpoint.

[0016] In this embodiment, non-limiting terms (eg, may, capable, or similar terms) refer to non-essential or optional implementations, inclusions, additions, or presences.

[0017] Unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. Furthermore, it should be understood that terms (e.g., terms defined in commonly used dictionaries) should be interpreted to have a meaning consistent with the meaning in the relevant technical context, and should not be interpreted in an idealized or overly formal sense unless expressly defined.

[0018] As used herein, a so-called "divalent organic group" is an organic group that has two bonding positions, and the "divalent organic group" is capable of forming two chemical bonds via these two bonding positions.

[0019] The present invention provides a resin composition, which contains, based on the total weight of the resin composition, 30% to 50% by weight of a bismaleimide (BMI) resin, 1% to 10% by weight of an epoxy resin, 1% to 10% by weight of a benzoxazine resin, 1% to 5% by weight of a hardener, 10% to 40% by weight of a filler, and 0.1% to 3% by weight of a coupling agent. The present invention combines the bismaleimide resin with the epoxy resin, the benzoxazine resin, the hardener, the filler, and the coupling agent, and can improve the heat resistance of the high frequency board material and reduce the dielectric constant and dielectric loss tangent of the high frequency board material.

[0020] In some embodiments, based on the total weight of the resin composition, the weight percentage of the bismaleimide resin is 30% to 50% by weight, such as 35%, 40%, or 45% by weight.

[0021] In some embodiments, the bismaleimide resin has a structure represented by formula (1): [ka] Here, L represents a dicyclopentadienyl group, a divalent organic group derived from a phenol compound, or a combination thereof; L 1 and L 2 represents a divalent organic group derived from a phenol compound, and m represents an integer of 0 to 18.

[0022] In some embodiments, the phenolic compound includes phenol. In some embodiments, the divalent organic group is preferably a divalent organic group including a maleimide group. In some embodiments, L is preferably a combination of dicyclopentadienyl and a divalent organic group derived from a phenolic compound. In some embodiments, L is preferably a structure represented by the following formula (1-1), a structure represented by the following formula (1-2), a structure represented by the following formula (1-3), or a combination thereof, * represents the attachment position. In some embodiments, L 1 and L2 Each of the formulas (1-4) represents a structure represented by the following formula: * represents the bond position. [ka]

[0023] In some embodiments, the bismaleimide resin has a structure represented by formula (2): [ka] Here, m represents an integer of 0 to 18, and preferably 2 to 10.

[0024] For example, the synthesis method of bismaleimide resin includes the following: First, 1 mole of dicyclopentadiene phenol resin (product name ERM6140, weight average molecular weight 1,300, manufactured by Songyuan Co., Ltd.) and 1.25 moles of 4-halonitrobenzene (wherein halogen can be fluorine, chlorine, bromine, or iodine) are added to 6 moles of dimethylacetamide (DMAC) used as a reaction solution, and reacted at a temperature of 120°C for 300 minutes to carry out a nitration reaction. Then, hydrogen gas is introduced to form a modified dicyclopentadiene-type diamine, and reacted at a temperature of 90°C for 480 minutes to carry out a hydrogenation reaction, thereby forming a modified dicyclopentadiene-based diamine. Next, to produce a second resin, which is a bismaleimide resin whose main chain contains a dicyclopentadiene structure (abbreviated as DCPD-BMI) and has a structure represented by formula (2) and whose average molecular weight may be 800 to 10,000, preferably 1,000 to 4,000, 3 moles of maleic anhydride and 9.7% by weight of toluenesulfonic acid are added and reacted at a temperature of 120°C for 420 minutes.

[0025] In some embodiments, the weight percentage of the epoxy resin is 1 wt% to 10 wt%, such as 2 wt%, 4 wt%, or 6 wt%, based on the total weight of the resin composition. In some embodiments, the epoxy resin is an epoxy resin offered under the trade name 437 by NANYA Plastics Industry Co., Ltd.

[0026] In some embodiments, the weight percentage of the benzoxazine resin is 1% to 10% by weight, such as 2%, 4%, or 6% by weight, based on the total weight of the resin composition. In some embodiments, the benzoxazine resin is a benzoxazine resin available from NANYA Plastics Industry Co., Ltd. under the trade name 234.

[0027] In some embodiments, the weight percentage of the curing agent is 1% to 5% by weight, such as 2%, 3%, or 4% by weight, based on the total weight of the resin composition. In some embodiments, the curing agent is a curing agent provided by DIC (Dainippon Ink and Chemicals, Inc.) under the trade name HPC-8000.

[0028] In some embodiments, the weight percentage of the filler is 10% to 40% by weight, such as 20%, 25%, or 30% by weight, based on the total weight of the resin composition. In some embodiments, the filler is spherical and the particle size (D50) of the filler is 0.3 μm to 3 μm. In some embodiments, the filler has a maximum particle size (D99) of 10 μm or less. In some embodiments, the filler includes a surface modification such as acrylic or vinyl. In some embodiments, the filler is SiO2, a filler provided by Sibelco Company.

[0029] In some embodiments, the weight percentage of the coupling agent is 0.1% to 3% by weight, such as 0.5%, 1%, or 1.5% by weight, based on the total weight of the resin composition. The addition of the coupling agent can increase the compatibility and crosslinking degree of the resin composition with the glass fiber cloth or powder. In some embodiments, the content of the coupling agent in the resin composition includes 0.1 parts (0.1 phr) to 5 phr of coupling agent per 100 parts by weight of resin. In some embodiments, the content of the coupling agent in the resin composition is 0.5 phr to 1 phr. In some embodiments, the coupling agent is a siloxane coupling agent. In some embodiments, the coupling agent is a vinyl silane or an acrylic silane. In some embodiments, the coupling agent is a coupling agent offered by DOW under the trade name Z-6030.

[0030] In some embodiments, the resin composition further comprises a flame retardant. In some embodiments, the weight percentage of the flame retardant is 5% to 15% by weight, such as 8%, 10%, or 12% by weight, based on the total weight of the resin composition. In some embodiments, the flame retardant is a phosphorus-based flame retardant. In some embodiments, the flame retardant is a flame retardant available from Daihachi Chemical Industry Co., Ltd. under the trade name PX200.

[0031] In some embodiments, the resin composition further comprises a catalyst. In some embodiments, the weight percentage of the catalyst is 0.1 wt% to 3 wt%, such as 0.5 wt%, 1 wt%, or 1.5 wt%, based on the total weight of the resin composition. In some embodiments, the content of the catalyst in the resin composition is preferably 0.5 phr to 1.2 phr. In some embodiments, the catalyst is a catalyst provided by ARKEMA under the trade name DCP.

[0032] The resin composition of the present invention is suitable for forming a substrate for an electronic component. In some embodiments, the substrate is a copper foil substrate. In some embodiments, the substrate has the following specifications: a dielectric constant (Dk) of about 3.5 or less, a dissipation factor (Df) of about 0.03 or less, a glass transition temperature (Tg) of greater than 260°C (e.g., about 260°C to 270°C), a peel strength of about 5 lb / in or more (e.g., about 5 lb / in to 6.5 lb / in), and / or a heat resistance that has passed the test.

[0033] The implementation and effects of the present invention will be described in detail below using copper foil substrates made of resin compositions of the present embodiment and comparative examples, although the present invention is not limited to the following embodiments and comparative examples.

[0034] Based on the composition ratio in Table 1 below, the resin composition is mixed with MEK to form a varnish of a thermosetting resin composition. The resulting varnish is impregnated into a Nanya glass fiber cloth (NANYA Plastics Industry Co., Ltd., cloth model 1078LD) at room temperature, and then dried at about 130°C (the temperature of the impregnation machine) for several minutes to obtain a prepreg having a resin content of 60% by weight. After that, four pieces of prepreg are laminated between two pieces of copper foil with a thickness of about 35 μm, and the laminate is heated to 25 kg / cm. 2 The mixture is kept at a temperature of 85°C under pressure for 20 minutes, heated to 210°C at a heating rate of 3°C per minute, kept at a constant temperature for 120 minutes, and then slowly cooled to 130°C to produce a 0.5 mm thick copper foil substrate.

[0035] In Examples 1 to 6, the "DCPD-BMI" used is a bismaleimide resin (DCPD-MI) having a structure represented by formula (2).

[0036] In Examples 2 to 4, "KI-50P" and "KI-70" used are bismaleimide resins of the KI-50P and KI-70 series, respectively, sold by KI Chemical Co., Ltd.

[0037] In Examples 1, 5, and 6, and Comparative Examples 2, 3, and 6, "MIR-3000" and "MIR-5000" used are bismaleimide resins of the MIR-3000 and MIR-5000 series, respectively, sold by Nippon Kayaku Co., Ltd.

[0038] In Comparative Examples 1 to 6, "BMI-1000" and "BMI-2300" used are bismaleimide resins of the BMI-1000 and BMI-2300 series, respectively, sold by Daiwa Fine Chemicals (Taiwan) Co., Ltd.

[0039] In Examples 1 to 6 and Comparative Examples 1 to 6, the "HPC-8000" used is a hardener sold by DIC (Dainippon Ink and Chemicals, Inc.) under the trade name HPC-8000.

[0040] In Examples 1 to 6 and Comparative Examples 1 to 6, the "DCP" used is a catalyst sold by ARKEMA under the trade name DCP series.

[0041] In Examples 1 to 6 and Comparative Examples 1 to 6, the "Z-6030" used is a siloxane coupling agent of the Z-6030 series, a trade name sold by DOW.

[0042] In Examples 1 to 6, the "437" used is an epoxy resin sold by NANYA Plastics Industry Co., Ltd. under the trade name of the 437 series.

[0043] In Comparative Examples 1 to 3, the "NC-3000-H" used is an epoxy resin in the NC-3000-H series, a product name sold by Nippon Kayaku Co., Ltd.

[0044] In Comparative Examples 4 to 6, the "HP-9000" used is an epoxy resin in the HP-9000 series, a trade name sold by DIC (Dainippon Ink and Chemicals, Inc.).

[0045] In Examples 1 to 6, Comparative Examples 1, 2, 4, and 6, the "234" used is a benzoxazine resin sold by NANYA Plastics Industry Co., Ltd. under the trade name 234 series.

[0046] In Comparative Examples 3 and 5, "BA-BXZ" used is a benzoxazine resin sold by Konishi Chemical Industry Co., Ltd. under the trade name BA-BXZ series.

[0047] In Examples 1 to 6 and Comparative Examples 1 to 6, the "PX200" used is a flame retardant in the PX200 series, a trade name of which is sold by Daihachi Chemical Industry Co., Ltd.

[0048] In Examples 1 to 6 and Comparative Examples 1 to 6, the SiO2 used is a SiO2 filler sold by Sibelco Company.

[0049] The copper foil substrate was evaluated for properties such as glass transition temperature, dielectric constant, dielectric loss tangent, peel strength, and heat resistance by the methods described below. The evaluation results are shown in Table 1.

[0050] Glass transition temperature (Tg)

[0051] The glass transition temperature (Tg) of the resin composition in the copper foil substrate was measured using a dynamic mechanical analyzer (DMA). A high Tg indicates that the resin composition has a good ability to resist phase change, i.e., good heat resistance.

[0052] Dielectric constant (Dk)

[0053] The dielectric constant at a frequency of about 10 GHz was measured using a dielectric analyzer (Model E4991A, manufactured by Agilent Technologies, Inc.) A small dielectric constant indicates that the resin composition in the copper foil substrate has good dielectric properties.

[0054] Dissipation factor (Df)

[0055] The dielectric loss tangent at a frequency of about 10 GHz was measured using a dielectric analyzer (Model E4991A, manufactured by Agilent Technologies, Inc.) A small dielectric loss tangent indicates that the resin composition in the copper foil substrate has good dielectric properties.

[0056] Peel strength

[0057] The peel strength between the prepreg and the copper foil was tested according to the IPC-TM-650-2.4.8 test method.

[0058] heat resistance

[0059] The copper foil substrate samples were heated in a pressure cooker at 120°C and 2 atm pressure for 120 minutes, then immersed in a soldering furnace at 288°C, and the time it took for the board to burst was recorded. Boards that took longer than 10 minutes to burst were marked as OK, and those that took less than 10 minutes were marked as NG.

[0060] [Table 1] JPEG2025031440000005.jpg178170

[0061] <Evaluation Results>

[0062] From Examples 1 to 6 in Table 1, it can be seen that the copper foil substrates made from the resin compositions having the component ratios of the present invention have Tg values ​​higher than 260° C., dielectric constants Dk values ​​less than 3.5, and dielectric loss tangents Df values ​​less than 0.003. Furthermore, the copper foil substrates of Examples 1 to 6 also exhibit good peel strength (≧5 lb / in) and good heat resistance.

[0063] From Comparative Examples 1 to 6 in Table 1, it can be seen that when the weight percentage of the bismaleimide resin is less than 30 weight % or more than 50 weight %, the weight percentage of the epoxy resin is more than 10 weight %, and the weight percentage of the benzoxazine resin is more than 10 weight %, the measured Tg value is lower than 260° C., the dielectric constant Dk is higher than 3.5, and the dielectric tangent Df is higher than 0.003. [Industrial Applicability]

[0064] In summary, the resin composition of the present invention has the property of not forming polar groups during the reaction, and is not easily polarized in an electric field, thereby greatly reducing the dielectric loss tangent. In addition, the resin composition of the present invention can be directly or indirectly applied to copper foil substrates and further processed into other household, industrial, or suitable electronic components or electronic products (e.g., circuit boards or copper foil substrates). In addition, when applied to copper foil substrates, the resin composition of the present invention benefits the improvement of glass transition temperature, the improvement of peel strength, the improvement of heat resistance, and / or the reduction of dielectric loss tangent.

Claims

1. Based on the total weight of the resin composition, 30% to 50% by weight of a bismaleimide resin; 1% to 10% by weight of an epoxy resin; 1% to 10% by weight of a benzoxazine resin; 1% to 5% by weight of a curing agent; 10% to 40% by weight of a filler; 1% to 3% by weight of a coupling agent; Including, Resin composition.

2. The bismaleimide resin comprises DCPD-BMI, KI-50P, KI-70, MIR-3000, MIR-5000, or a combination thereof; The resin composition according to claim 1.

3. The weight percentage of the epoxy resin is 1% to 3% by weight; The resin composition according to claim 1.

4. Further comprising 0.1 wt.% to 3 wt.% of a catalyst; The resin composition according to claim 1.

5. Further comprising 5% to 15% by weight of a flame retardant; The resin composition according to claim 4.

6. A substrate formed from the resin composition according to claim 1. Electronic components.

7. The substrate has a dielectric constant of 3.5 or less at a frequency of about 10 GHz. The electronic component according to claim 6.

8. the substrate has a dielectric loss tangent of 0.003 or less at a frequency of about 10 GHz; The electronic component according to claim 6.

9. The glass transition temperature of the substrate is 260° C. or higher. The electronic component according to claim 6.

10. The substrate is a copper foil substrate; The electronic component according to claim 6.

Citation Information

Patent Citations

  • Thermosetting resin composition and prepreg, laminated board, circuit substrate and printed circuit board containing same

    CN114605780A

  • Silicon carbide, gallium oxide, gallium nitride, and molding material composition for sealing diamond element, and electronic component device

    JP2020145424A

  • Thermosetting resin composition for semiconductor packaging and prepreg using the same

    JP2020528471A

  • Benzoxazine resin, production method of the same, and resin composition

    JP2022108705A

  • Thermosetting resin composition, and prepreg, metal foil-clad laminate, and printed circuit board containing the same

    JP2022515262A